The problems of the sectoral development of agriculture in Kazakhstan in the framework of food security (Journal of Economic Research & Business Administration, 2016)
Nowadays growing of the world population food provision today, becomingone of the most pressing issues. The development of agriculturewill increase food security of population, diversify exports in terms of lowprices for oil, gas and other natural resources; will reduce inflation in themarket, improve the condition of the financial and monetary system. In thisregard, it is important to diversify the agricultural sector and the definitionof the direction of development, increasing productivity and competivenessof the sector based on innovative technologies. In our country thereare all the economic and climatic conditions to ensure an environmentallyfriendly and high-quality food. Therefore, the development of agricultureshould be considered as a package.This article contains a statistical analysis of the issues of agriculturalindustry with the framework of food security, proposed scientific and innovativemethods to improve performance, consider mechanisms to supportthe domestic market and export directions to foreign markets.
Keywords: agro industrial complex; food security; subsidies; import; export; production technologies and infrastructure.